2007
DOI: 10.1186/1471-2377-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome following acute ischaemic stroke relates to both activation and autoregulatory inhibition of cytokine production

Abstract: Background: As critical mediators of local and systemic inflammatory responses, cytokines are produced in the brain following ischaemic stroke. Some have been detected in the circulation of stroke patients, but their role and source is unclear. Focusing primarily on interleukin(IL)-1-related mechanisms, we serially measured plasma inflammatory markers, and the production of cytokines by whole blood, from 36 patients recruited within 12 h and followed up to 1 year after acute ischaemic stroke (AIS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 43 publications
5
59
1
Order By: Relevance
“…Our preliminary trial of IL-1RA in stroke patients supports this view in that it showed a reduction in plasma IL-6, as well as C-reactive protein and the leukocyte cell count (Emsley et al, 2005). Since the most likely source of increased plasma IL-6 after stroke is the central nervous system (Emsley et al, 2007), this suggests that IL-1RA has an impact on IL-6 induction in the brain. Although our trial in stroke hinted at clinical efficacy, it was too small to provide sufficient evidence of this.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our preliminary trial of IL-1RA in stroke patients supports this view in that it showed a reduction in plasma IL-6, as well as C-reactive protein and the leukocyte cell count (Emsley et al, 2005). Since the most likely source of increased plasma IL-6 after stroke is the central nervous system (Emsley et al, 2007), this suggests that IL-1RA has an impact on IL-6 induction in the brain. Although our trial in stroke hinted at clinical efficacy, it was too small to provide sufficient evidence of this.…”
Section: Discussionsupporting
confidence: 65%
“…Growing evidence implicates inflammation and inflammatory molecules such as interleukin (IL)-1 in central nervous system disease (Lipton, 1999;Ginsberg, 2002;Allan and Rothwell, 2003;Lees et al, 2006;Emsley et al, 2007). This cytokine is induced rapidly in response to experimental brain insults and, when administered to rodents centrally or peripherally, enhances brain injury (Rothwell et al, 1997a, b;Allan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of proinflammatory cytokines was detected in early atherogenesis, atheroma formation, and thrombosis, the last complication of atherosclerosis responsible for myocardial infarction and most strokes 4 . Moreover, these inflammatory mediators are considered to be responsible for recruiting leukocytes to the ischemic area after stroke 5 . Interleukin 1 (IL-1) is the prototypic inflammatory cytokine with widespread impact on neural function.…”
mentioning
confidence: 99%
“…Since inflammation generates the formation of edema and can promote apoptosis, inflammatory biomarkers are potentially useful for prognosis and as prospective targets for neuroprotective therapies [9]. Although none of the cytokines that activate in the brain following stroke are CNS specific, careful investigation has confirmed that the elevation in plasma levels of these signaling molecules is owing to their production in the CNS and not from peripheral blood cells [10]. The aim of this study was to measure the serum IL-6 serially in acute ischemic stroke patients and to see the correlation of it's baseline levels with stroke severity and outcome.…”
Section: Resultsmentioning
confidence: 99%